Study of a Novel Bisnaphthalimidopropyl Polyamine as Electroactive Material for Perchlorate‐selective Potentiometric Sensors. Issue 12 (16th July 2015) - Gil, Renato; Amorim, Célia G.; Crombie, Laura; Kong Thoo Lin, Paul; Araújo, Alberto; da Conceição Montenegro, Maria
Abstract: In this work, the new polyamine bisnaphthalimidopropyl‐4, 4'‐diaminodiphenylmethane is proposed as a new ionophore for perchlorate potentiometric sensors. The optimal formulation for the membrane comprised of 12 mmol kg −1 of the ionophore, and 68 % (w/w) of 2‐nitrophenyl phenyl ether as plasticizer and 31 % (w/w) of high molecular weight PVC. The sensors were soaked in water for a week to allow leakage of anionic impurities and for one day in a perchlorate solution (10 −4  mol L −1 ) to improve reproducibility due to its first usage. The stability constant for the ionophore‐perchlorate association in the membrane, log β IL1 =3.18±0.04, ensured a performance characterized by the slope of 54.1 (±0.7) mV dec −1 to perchlorate solutions with concentrations between 1.24×10 −7 and 1.00×10 −3  mol L −1 . The sensors are insensitive to pH between 3.5 to 11.0, they have a practical detection limit of 7.66 (±0.42) ×10 −8  mol L −1 and a response time below 60 s for solutions with perchlorate concentrations above 5×10 −6  mol L −1 . The accuracy of the results was confirmed by the analysis of the contaminant in a certified reference water sample. Abstract :